Safety and efficacy of a feed additive consisting of Bacillus paralicheniformis DSM 33902 and Bacillus subtilis DSM 33903 (Bovacillus™) for dairy cows and other dairy ruminants (Chr. Hansen A/S) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Bovacillus™, a product containing viable cells of Bacillus paralicheniformis DSM 33902 and Bacillus subtilis DSM 33903, which is intended to be used as a zootechnical additive (functional group: gut flora stabiliser) in the feed of dairy cows and other dairy ruminants. The trade name is Bovacillus™, and it is intended to be commercialised in two formulations: Bovacillus™ 10, to use in feed, and WS, to use in drinking water. B. paralicheniformis and B. subtilis are considered suitable for the qualified presumption of safety (QPS) approach to safety assessment. The identity of the active agents was established, and compliance with the applicable qualifications confirmed. Therefore, Bacillus paralicheniformis DSM 33902 and Bacillus subtilis DSM 33903 are presumed safe for the target species, consumers of products derived from animals fed the additive and the environment. Since no concerns are expected from the other components of the additive, Bovacillus™ is also considered safe for the target species, consumers and the environment. Bovacillus™ 10 and WS are not skin or eye irritants. Due to the nature of the active agents, both forms of the additive are considered respiratory and skin sensitisers. The Panel concludes that Bovacillus™ has the potential to be efficacious as a zootechnical additive when supplemented in the feed of dairy ruminants at 3.8 × 108 CFU/kg complete feed.